How multilateral environmental regimes affect policies for forest conservation and ecosystem services provision: The case of Costa Rica - Muñoz Brenes, Carlos Luis (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Costa Rica's success in promoting conservation policies has emanated from a strategic reading and adaptive capacity to multilateral environmental agreements (MEAs) in combination with the collective action between the state and major actors in civil society and across the border. A strategic reading implies institutional changes from collective action and adaptability to feedbacks from the agents in the social and ecological systems. The policymaking process had a strong reaction to the international environmental agreement negotiations. Policies established from the 1970s to 1996 had ambiguous effects on development. There is clear evidence that forest conservation policies and institutional changes in the late 1980s were influenced by international agreements. Such changes fostered a development path that closely resembles the notion of sustainability; forest ecosystems services contribute to ecotourism, agriculture, energy sectors, and improvement of people's livelihoods. Further, national policy innovation had a spillover effect at the international level. Externally, actors in the global domain saw the Costa Rican experience as replicable or adaptable to other social and economic contexts, the international climate change agenda provides a fertile ground to experiment on how MEAs contribute to changes in domestic policy and how these regimes can also be influenced by successful policies. The REDD negotiations provide strong evidence that supports the idea of the emergence of a global ecosystem service regime which allows public, private, and international transaction to take place around ecosystem services. Such regime may also help give coherence to a global system of environmental governance.